Eustachian tube functional assessment among patients with CSOM undergoing tympanoplasty surgery - P., Hemalatha; V. J., Vikram (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Pre-operative test of eustachian tube (ET) function is important for achieving a satisfactory result of tympanoplasty for CSOM patients. The saccharin test and methylene blue test seems to provide adequate information of the mucociliary function and patency of the ET. The aim was to study the ventilatory and mucociliary function of Eustachian tube in patients with chronic suppurative otitis media planned for tympanoplasty surgery and to assess the success rate of tympanoplasty in relation to the Eustachian tube function Methods: A prospective longitudinal study was conducted for a period of one year. Patients aged more than 15 years with features of chronic suppurative otitis media of either tubotympanic type or atticoantral type were included in the study. The total number of study subjects included in our study was 82 patients with CSOM. The ventilatory and the mucociliary functions of the auditory tube were assessed preoperatively using saccharin test and methylene blue test. All patients with CSOM underwent tympanoplasty surgery and the outcome of the surgery was assessed. Results: The overall success rate of tympanoplasty surgery was 76.8%. It was observed in our study that the success rate of tympanoplasty was higher among patients with normal eustachian tube function. Conclusions: Preoperative evaluation of eustachian tube function is mandatory for all the patients planned for tympanoplasty. Preoperative and intraoperative corrective measures should be taken in patients with partial and absent tubal function to improve the success rate of tympanoplasty surgeries.